Data Accounting: Data as a New Corporate Asset in the Perspective of Modern Accounting - Tikkos Sitanggang (Pt. Anagata Sembagi Education, 2026)
The digital economy has elevated data to the status of a strategic corporate resource, yet conventional accounting frameworks lack systematic mechanisms for recognizing, measuring, and disclosing data as a formal asset on financial statements. This study investigates the extent to which Indonesian publicly listed companies recognize and disclose data assets, and examines the relationship between data asset accounting maturity and corporate financial performance. Using a mixed-methods design involving a survey of 312 financial reporting professionals from Indonesia Stock Exchange (IDX) Main Board companies and a qualitative documentary analysis of 60 annual reports, the study finds that only 38.5% of sampled firms formally recognize data as a balance sheet asset, despite 91.3% acknowledging data's strategic value. Data asset accounting maturity significantly predicts return on assets (β=0.487, p<0.001) and market-to-book ratio (β=0.531, p<0.001). Critical barriers include the absence of authoritative PSAK/IFRS standards for data asset recognition, valuation model ambiguity, and insufficient interdisciplinary accounting-technology competencies. The study proposes a Data Asset Accounting Framework (DAAF) integrating cost, income, and market valuation approaches with enhanced disclosure requirements.